Successful Treatment of Uncomplicated Gonococcal Urethritis in HIV-Infected Patients with Single-Dose Oral Cefpodoxime - George Psevdos; Victoria Sharp (Canadian Journal of Infectious Diseases and Medical Microbiology)
Fluoroquinolones are no longer recommended for the treatment of gonococcal infections in the United States. Cephalosporins – ceftriaxone and cefixime – are the treatment of choice, as suggested by the Centers for Disease Control and Prevention (USA). There are limited data on the efficacy of cefpodoxime for the treatment of uncomplicated gonococcal infections. Two cases of HIV-infected homosexual men who were successfully treated with cefpodoxime for urethritis caused by Neisseria gonorrhoeae are described in the present study.